Hyoscyamus albus (Solanaceae): A new distributional record for India - Swamy, J.; Annamma, P. S.; Chandra Mohan, K.; Rasingam, L. (Rheedea, 2015)
Hyoscyamus albus L. is reported here for the first time for India from Hyderabad, Telangana. A detailed description, notes and photographs are provided for easy identification.